2021
DOI: 10.1371/journal.pone.0245784
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of forage biomass and vegetation cover in grasslands using UAV imagery

Abstract: Grasslands are among the most widespread ecosystems on Earth and among the most degraded. Their characterization and monitoring are generally based on field measurements, which are incomplete spatially and temporally. The recent advent of unmanned aerial vehicles (UAV) provides data at unprecedented spatial and temporal resolutions. This study aims to test and compare three approaches based on multispectral imagery acquired by UAV to estimate forage biomass or vegetation cover in grasslands. The study site is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 43 publications
2
26
0
1
Order By: Relevance
“…Other previous studies have indicated that NDVI is more commonly used for pasture biomass measurements [88,89], as well as in larger-scale grassland followed by seasonal monitoring [90]. However, the findings of this study indicate that NDVI may not be the most suitable VI, which was supported by a previous study [86]. This highlights the importance of considering the saturation, sensitivity, stages of crop development, canopy structure, and the type of environment when testing various vegetation indexes [15].…”
Section: Importance Of Variable Rankingssupporting
confidence: 51%
See 1 more Smart Citation
“…Other previous studies have indicated that NDVI is more commonly used for pasture biomass measurements [88,89], as well as in larger-scale grassland followed by seasonal monitoring [90]. However, the findings of this study indicate that NDVI may not be the most suitable VI, which was supported by a previous study [86]. This highlights the importance of considering the saturation, sensitivity, stages of crop development, canopy structure, and the type of environment when testing various vegetation indexes [15].…”
Section: Importance Of Variable Rankingssupporting
confidence: 51%
“…Different VI values at the level of leaf area indices were likely caused by the diverse canopy structures of clover (horizontal) and grass leaves (vertically orientated) [71]. A recent study confirmed that GNDVI is suitable as a biomass predictor for perennial forage crops, where R 2 = 0.80 for freshly-cut, and 0.66 for dry yields [86], as well as in the grain yield estimation in maize [87]. These results resemble the RFR and ANN modelling of this study, where the GNDVI, GDVI, and MSR had the highest average contributions.…”
Section: Importance Of Variable Rankingsmentioning
confidence: 96%
“…All three models allow fine spatial resolution. In this case, the use of RGB imagery gave better agreement with the data collected by conventional methods of sampling and characterization of biomass compared to volumetric measurement because it allows to distinguish between living and dead biomass (ie photosynthetically active and dried plants) [11]. Such models are suitable for monitoring the spatial distribution of biomass but are not sufficiently usable in relation to the time scale.…”
Section: Data Processing and Analysis Methodsmentioning
confidence: 93%
“…Figure 5 -Comparison of the representation of the same experimental field of sorghum by different models: a -RGB, b -volumetric model, c -GNDVI for biomass,d -GNDVI for vegetation cover[11] …”
mentioning
confidence: 99%
“…In this sense, LiDAR sensors on-board unmanned aerial vehicles (UAV-LiDAR) allows for acquiring higher point density than traditional airborne LiDAR [128,129]. Simultaneous acquisition of UAV multispectral imagery (UAV-MS) at very high spatial resolution also allows for improving the classification of ground/non-ground returns of UAV-LiDAR data in areas with low vegetation and rough topography [95,130] and discriminating dead standing and lying biomass [131,132]. Therefore, UAV consumer-grade technology may enhance ACD estimation in shrubland ecosystems and should be considered in future research.…”
Section: Uncertainties and Research Implicationsmentioning
confidence: 99%